Pain and symptom control in palliative care: new ways to think about old drugs - Driver, Larry (Henry Stewart Talks, 2009)
Medical decision making, Cancer patients' symptom burden, Why treat pain?, Cancer pain: a significant problem, Pain affects patients throughout the disease course, Causes of pain in cancer patients, Pain definitions and pathophysiology, Consequences of inadequately managed pain, Relating pain with function, Pain and symptom assessment, ABCs of pain and symptom assessment and management, Therapeutic approaches, Pharmacotherapy, Commonly prescribed opioids, Principles of opioid therapy for effective pain management, NCCN guidelines for adult cancer pain, Extended- and regular-released opioids, Methadone, Opioid adverse effects, Opioid rotation, Managing the poorly responsive patient, Adjuvant analgesics/co-analgesics, Procedural interventions, Nonpharmacologic treatment, Collateral opioid issues, Cancer fatigue, Treatment of fatigue, Cancer anorexia-cachexia, Progestational agents, Psychotropic agents, Anabolic agents, Chronic nausea/vomiting, Nausea management, Anti-emetic agents